2012
DOI: 10.1095/biolreprod.111.094748
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NADPH Oxidase by Trophoblast Cells: Potential Implications for the Postimplanting Mouse Embryo1

Abstract: Cytochemical localization of hydrogen peroxide-generating sites suggests NADPH (nicotinamide adenine dinucleotide 3-phosphate [reduced form]) oxidase expression at the maternal-fetal interface. To explore this possibility, we have characterized the expression and activity of the NADPH oxidase complex in trophoblast cells during the postimplantation period. Implantation sites and ectoplacental cones (EPCs) from 7.5-gestational day embryos from CD1 mice were used as a source for expression analyses of NADPH oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
3
9
0
1
Order By: Relevance
“…The H2O2 production from the surface of trophectodermal cells is proposed to participate in the interaction of hatched blastocyst and the endometrium in the decidual response (Manes and Lai, 1995) due to Nox activity. All the components required for the Nox complex are expressed in the trophectodermal cells (Gomes et al, 2012) supporting the proposal that ROS also participate in the implantation of the blastocyst (Bevilacqua et al, 2012).…”
Section: Oxygen and Ros In Animal Developmentsupporting
confidence: 75%
“…The H2O2 production from the surface of trophectodermal cells is proposed to participate in the interaction of hatched blastocyst and the endometrium in the decidual response (Manes and Lai, 1995) due to Nox activity. All the components required for the Nox complex are expressed in the trophectodermal cells (Gomes et al, 2012) supporting the proposal that ROS also participate in the implantation of the blastocyst (Bevilacqua et al, 2012).…”
Section: Oxygen and Ros In Animal Developmentsupporting
confidence: 75%
“…Still in mice, but in later gestational stages, neither NADPH oxidase nor XO inhibitors are able to completely abolish ROS production in ectoplacental cone cells: these findings indicate that both ROS production systems are active in trophoblast cells (Gomes et al, 2011). In addition, studies focusing on antioxidant defences in the rat placenta showed increased placental activity of XO between gd16 and 22, suggesting that placental XO-mediated ROS generation increases in late gestation (Jones et al, 2010).…”
Section: Xanthine Oxidasementioning
confidence: 90%
“…The molecular characterization of the mouse trophoblast NADPH oxidase that gives greater insight into the functional enzymic activity in placental tissues comes from Gomes et al (2011). They have shown that ectoplacental cone cells express the essential elements for the activation of NADPH oxidase: the membrane subunits, gp91phox and p22phox that contain the catalytic domain in the enzyme; the cytosolic subunits p40phox that can function as a regulatory factor; p47phox whose phosphorylation is essential for the enzyme activation; p67phox (an obligatory component); and the G-protein Rac1, reinforcing the potential enzymic activity of the trophoblast.…”
Section: Nadph Oxidase and Ros Generation At The Maternal-fetal Interfacementioning
confidence: 99%
“…The inhibitory action of apocynin on the effects on HG indicates an important role of NOX in mediating the effects of HG. Functional NOX has been observed in mouse ectoplacental cones of 7.5 GD conceptuses and in cultured TGCs derived from these cones (Bevilacqua, Hoshida, Amarante‐Paffaro, Albieri‐Borges, & Gomes, , Gomes et al, ). ROS generation by NOX has been associated with the phagocytic activity of the post‐implantation trophoblast (Gomes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional NOX has been observed in mouse ectoplacental cones of 7.5 GD conceptuses and in cultured TGCs derived from these cones (Bevilacqua, Hoshida, Amarante‐Paffaro, Albieri‐Borges, & Gomes, , Gomes et al, ). ROS generation by NOX has been associated with the phagocytic activity of the post‐implantation trophoblast (Gomes et al, ). In this study, apocynin prevented the HG‐induced increases in PLAU, PAI‐1, and MMP‐9 expression, decreasing trophoblast spreading.…”
Section: Discussionmentioning
confidence: 99%